2D van der Waals Heterojunction of Organic and Inorganic Monolayers for High Responsivity Phototransistors. (24th July 2021) - Zhao, Baolin; Gan, Ziyang; Johnson, Manuel; Najafidehaghani, Emad; Rejek, Tobias; George, Antony; Fink, Rainer H.; Turchanin, Andrey; Halik, Marcus
Abstract: Van der Waals (vdW) heterostructures composing of organic molecules with inorganic 2D crystals open the door to fabricate various promising hybrid devices. Here, a fully ordered organic self‐assembled monolayer (SAM) to construct hybrid organic–inorganic vdW heterojunction phototransistors for highly sensitive light detection is used. The heterojunctions, formed by layering MoS2 monolayer crystals onto organic [12‐(benzo[b]benzo[4, 5]thieno[2, 3‐d]thiophen‐2‐yl)dodecyl)]phosphonic acid SAM, are characterized by Raman and photoluminescence spectroscopy as well as Kelvin probe force microscopy. Remarkably, this vdW heterojunction transistor exhibits a superior photoresponsivity of 475 A W −1 and enhanced external quantum efficiency of 1.45 × 10 5 %, as well as an extremely low dark photocurrent in the pA range. This work demonstrates that hybridizing SAM with 2D materials can be a promising strategy for fabricating diversified optoelectronic devices with unique properties. Abstract : A highly ordered organic semiconducting self‐assembled monolayer (SAM) with transition metal dichalcogenides is integrated into fully 2D organic–inorganic hybrid van der Waals heterostructures. The ordered nature of the SAM results in efficient exciton dissociation at the interface. The phototransistors show a superior photoresponsivity (475 A W −1 ), which benefits from the precise confinement of charge in the monolayers and a strong photogating effect.